Video Tutorials for Strengthening English in a New School in the Municipality of Oiba, Santander - Melgarejo Leon, Kevin Andrey (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Teaching English is fundamental in a society that is becoming more globalized each day. Throughout this manuscript, I present a study about creating video tutorials to enhance the English language in a Progressive Education Setting in Oiba Santander. Six video tutorials about tech tools and in-class flip for the English classroom were presented to nine teachers who were the participants in this qualitative study. An interpretative paradigm and action research were the basis to carry out this study. Interviews and field diaries were fundamental data collection instruments used. After applying the interventions of this project, some relevant conclusions were obtained due to the application of video tutorials that explained the in-class flip approach and digital tools. The findings revealed that teachers moved from having a minimum usage of tech-tools to be willing to include them in their future teaching practices, Additionally, teachers were intrigued about the content of future videos.